2016
DOI: 10.18632/oncotarget.13439
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effects of nilotinib prophylaxis after allogeneic stem cell transplantation in patients with advanced chronic myeloid leukemia or philadelphia chromosome-positive acute lymphoblastic leukemia

Abstract: Allogeneic stem cell transplantation remains the standard treatment for resistant advanced chronic myeloid leukemia and Philadelphia chromosome–positive acute lymphoblastic leukemia. Relapse is the major cause of treatment failure in both diseases. Post-allo-SCT administration of TKIs could potentially reduce relapse rates, but concerns regarding their effect on immune reconstitution have been raised. We aimed to assess immune functions of 12 advanced CML and Ph+ ALL patients who received post-allo-SCT nilotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Varda-Bloom et al [26] (n = 12) studied the effects of nilotinib after allo-HSCT in patients with CML (n = 7) and Ph+ ALL (n = 5) ( Table 3). Nilotinib was administered in doses ranging from 200 to 300 mg twice daily.…”
Section: Overview Of Prospective Trials With Nilotinibmentioning
confidence: 99%
See 1 more Smart Citation
“…Varda-Bloom et al [26] (n = 12) studied the effects of nilotinib after allo-HSCT in patients with CML (n = 7) and Ph+ ALL (n = 5) ( Table 3). Nilotinib was administered in doses ranging from 200 to 300 mg twice daily.…”
Section: Overview Of Prospective Trials With Nilotinibmentioning
confidence: 99%
“…The OS and EFS/DFS at 7.5 months to 2 years ranged from 69% to 84% and 56%to 84%, respectively. The third trial reported EFS and OS at 5 years of 60% each in patients with Ph+ ALL [26].…”
Section: Overview Of Prospective Trials With Nilotinibmentioning
confidence: 99%
“…The OS of the remaining two patients was 10.2 and 32.5 months. 108 A similar study of 16 patients with CML/ALL patients reported a 2-year OS of 69% and PFS of 56%. 109 Dasatinib, also a second-generation TKI, has the most published retrospective studies of Ph+ ALL patients.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 91%
“…Nilotinib, a second-generation TKI, has also been prospectively studied as maintenance postallo-HCT; however, these trials include patients with CML or ALL. 108,109 A small study of 12 patients (5 ALL) reported 3/5 Ph+ patients with ALL were alive and remained in CR 5-8 years after allo-HCT. The OS of the remaining two patients was 10.2 and 32.5 months.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…TKI therapy after allo-SCT may affect or hinder the immune reconstitution after transplant. A recent study of a small series of patients found that nilotinib prophylaxis after allo-SCT in patients with advanced CML or Philadelphia chromosome-positive acute lymphoblastic leukemia did not jeopardize immune reconstitution or function following transplantation [8]. Further studies must evaluate the role of TKI therapy as prophylactic therapy or preemptive therapy triggered by the detection of minimal residual disease, in the posttransplantation setting in transplant-eligible CML patients.…”
mentioning
confidence: 99%